A bipolar pyridine-functionalized porphyrin with hybrid charge-storage for dual-ion batteries. Issue 19 (14th February 2023) - He, Fangfang; Zhou, Yangmei; Chen, Xi; Wang, Ting; Zeng, Youlian; Zhang, Jiahao; Chen, Zhi; Liu, Wei; Gao, Ping
Abstract : A metal-free pyridine functionalized porphyrin is proposed as a new electrode for organic batteries with long-term cycling stability and high-power density. Abstract : A metal-free porphyrin T4PP with a pyridine group is proposed as a new electrode for lithium/sodium-based dual-ion batteries (LDIBs/SDIBs). The electrochemical performance and reaction mechanism of T4PP are explored thoroughly. The extended porphyrin conjugated structure by the pyridine groups enables an excellent cycle life (5000 cycles) and a high-power density (18.7 kW kg −1 ). A hybrid charge-storage mechanism with the contribution of both cations and anions benefits fast charge transfer.